60 lat "Czwartków Lubuskich" w Wojewódzkiej i Miejskiej Bibliotece Publicznej w Zielonej Górze = 60 years of ?Czwartki Lubuskie? (Lubusz Thursdays) at the Cyprian Norwid Regional and City Public Libraryin Zielona Góra - Rudiak, Robert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Meetings with authors, lectures, readings and, above all, literary evenings promoting books by authors from the Lubusz Region, held under the name ?Czwartki Lubuskie?, have been organized by the Cyprian Norwid Regional and City Public Library in Zielona Góra for over sixty years. During the many high-profile literary events and meetings with writers, poets, journalists, historians, and travelers, several hundred authors have been invited, from both the Lubusz Region and neighboring provinces, as well as from Poland more generally and from abroad. In the period1956-2016 (with a 12-year break from 1981 to 1993, when the organization of ?Thursdays? was discontinued after martial law was imposed), almost 800 meetings were held. Among the best-known writers were authors of world bestsellers, such as William Wharton and Jonathan Carroll as well as recognized Polish writers, including Tadeusz Różewicz, the priest Jan Twardowski, Władysław Broniewski and Melchior Wańkowicz. During meetings with authors originating from the Lubusz region about 300 titles of books have been promoted. The institution of ?Czwartki Lubuskie? has become a well-known and highly valued cultural brand of the Lubusz region.
Keywords: Czwartki Lubuskie; biblioteka publiczna; imprezy literackie; kultura i sztuka; Wojewódzka i Miejska Biblioteka Publiczna im. C. Norwida w Zielonej Górze; Thursdays in Lubusz Province; public library; literary events; culture and art; The Cyprian Norwid Regional and City Public Library in Zielona Góra